Chromosomal location of four genes encoding Class III peroxidases in wheat - Simonetti, Ester (2012)
In previous work, deduced amino acid sequences from twenty wheat peroxidase genes were assigned to seven groups designated as TaPrx108 to TaPrx114. Some of these apoplastic peroxidases, have previously shown to play different roles in the plant defense responses to infection by the cereal cyst nematode Heterodera avenae. In the present study, PCR marker analysis using Sears’s aneuploid wheat lines cv. ‘Chinese Spring’, was used to locate four genes encoding peroxidase isozymes. The TaPrx111-A, TaPrx112-D and TaPrx113-F genes were located on the short arm of chromosome 2B and the TaPrx109-C on the long arm of chromosome 1B. These results would agree with the synteny between wheat and rice chromosomes previously established in other studies.